Therapeutic Effect of Intense Pulsed Light on Ocular Demodicosis. (4th March 2019) - Zhang, XiaoZhao; Song, Nan; Gong, Lan
ABSTRACT: Purpose : To evaluate the clinical efficacy of Lumenis® M22 TM intense pulsed light (IPL) in reduction of ocular Demodex infestation in eyelashes in a prospective study. Methods : Forty patients with ocular demodicosis were recruited. Then half were randomly picked to receive the IPL treatment, while the other half got 5% tea tree oil (as the control group). Demodex counts, the ocular surface disease index (OSDI) score, lid margin abnormalities, conjunctival congestion, tear break-up time (TBUT), corneal staining with fluorescein, meibomian gland (MG) expressibility, meibum quality, modified Schirmer I test with anaesthetic (SIT), were assessed on the day before treatment and after treatment of 30 and 90 days, respectively. Changes in the parameters were compared between the IPL group and the control group on the days after treatment of 30 and 90 days. Results : No differences were observed in Demodex counts, lid margin abnormalities, conjunctival congestion, corneal staining with fluorescein, MG expressibility, SIT in the two groups on the days after treatment of 30 and 90 days ( p  > 0.05), whereas there was a statistically significant difference in the OSDI score, TBUT, meibum quality ( p  < 0.05). The Demodex eradication rate was more thorough in the IPL group (100%) than in the control group (75%). Conclusions : IPL shows the preferably therapeutic potential for ocular Demodicosis.